STATUS MUTU AIR DAERAH ALIRAN SUNGAI DI KABUPATEN BERAU PROVINSI KALIMANTAN TIMUR - Rizal, Muhammad Syamsur; Sofia, Leila Ariyani; Asmawi, Suhaili; Suyanto, Suyanto (Universitas Lambung Mangkurat, 2023)
The watershed in Berau Regency is used as an economic route and means of transportation of goods from mining, plantations, and agriculture as well as a source of raw materials for making drinking water. the water quality of the Berau watershed based on the value of the River Water Pollution Index in Berau Regency includes light pollution. This is a concern to conduct research in the Berau watershed, where this study aims to analyze the status of water quality according to the IP (Pollution Index) method and the economic value of watersheds in Berau Regency for the people of Berau Regency and compile recommendations for pollution control and watershed utilization in Berau Regency.The calculation uses the Pollution Index (IP) method of watershed quality status in Berau Regency consisting of Segah River, Kelay River, and Sungi Berau is in Light Pollution condition with a value of (1.75 ≤ IP ≤ 4.97) with a tendency for Berau River to have a greater pollution burden.